THE EFFECT OF WORKLOAD AND MOTIVATION ON EMPLOYEES’ PERFORMANCE THROUGH JOB STRESS AS A MEDIATING VARIABLE: PENGARUH BEBAN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI MELALUI STRESS KERJA SEBAGAI VARIABEL MEDIASI - Salahudin; Natsir, Syahir; Adda, Harnida Wahyuni (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2023)
The purpose of this study was to determine the impact of Workload and Motivation on Employee Performance through Work Stress as a Mediating Variable (Study at the Central Sulawesi Provincial Statistics Agency). The subjects in this study were employees of the Central Sulawesi Provincial Statistics Agency and the sample of this study were employees at the Central Sulawesi Provincial Statistics Agency Office, totaling 56 people. The sampling technique in this study used Purposive Sampling technique. The data were analyzed by SEM analysis assisted by the SmartPLS3 application. The results of this study indicate that there are 5 (five) direct relationships between influencing variables. The results of the variables that affected directly are: workload has a significant effect on employee performance, it has a significant effect on work stress, work motivation has a significant effect on employee performance, work motivation has a significant effect on work stress, and work stress directly has a significant effect on employees’ performance. The results of the analysis of variables that affected indirectly are: workload indirectly has a significant effect on employee performance through work stress and work motivation indirectly has a significant effect on employee performance through work stress